2013
DOI: 10.1149/2.077304jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Deposition of Mn:ZnO Films under Hydrothermal Conditions

Abstract: This study demonstrated the electrochemical deposition of Mn-doped ZnO films under hydrothermal conditions at 130 • C in 50% v/v DMSO-H 2 O mixture. X-ray diffraction analysis showed that the deposition of the ZnO structures was along (002) direction. However, the presence of Mn 2+ affected the thickness of ZnO structures and we believe that the interaction of Mn 2+ with the nonpolar surface of ZnO restricts lateral growth. Mn appears in the mixed oxide state in ZnO lattice. The photoluminescence spectra of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…1. A deposition bath containing only 50 mM Zn(NO 3 ) 2 in 1:1 DMSO: H 2 O mixture gives rise to the formation of thin platelets with about 1-2-lm-sized edges as shown in our previous study (Yilmaz and Unal 2013). Similar morphology was observed for the film grown from the bath containing Zn(NO 3 ) 2 and Co(NO 3 ) 2 with a [Co(II)]: [Zn(II)] ratio of 0.2.…”
Section: Morphology and Structuresupporting
confidence: 56%
See 3 more Smart Citations
“…1. A deposition bath containing only 50 mM Zn(NO 3 ) 2 in 1:1 DMSO: H 2 O mixture gives rise to the formation of thin platelets with about 1-2-lm-sized edges as shown in our previous study (Yilmaz and Unal 2013). Similar morphology was observed for the film grown from the bath containing Zn(NO 3 ) 2 and Co(NO 3 ) 2 with a [Co(II)]: [Zn(II)] ratio of 0.2.…”
Section: Morphology and Structuresupporting
confidence: 56%
“…Effect of additives is significantly influenced by high-temperature electrodeposition with each cation and anion behaving differently. It has been presented that by adjusting [MnCl 2 ] in the deposition bath, diameters of ZnO rods can be tuned by HED (Yilmaz and Unal 2013). In the following study, we have shown that besides precursor concentration, identities of the additive metal cation and counter ion in the deposition solution are important to produce ZnO particles with various morphologies.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The method combines one step production of oriented ceramics with high growth rate [18]. Deposition of various ceramics and double oxides such as ZnO [19][20][21][22], LiCoO 2 [23], and LiNiO 2 [24] with this technique were reported previously. Regarding manganese oxides, Hill et al conducted systematic studies on hydrothermalelectrochemical deposition of manganese oxides (mainly MnO 2 ) [25][26][27][28].…”
mentioning
confidence: 99%